Influence of the conductivity of the magnetoelectric composites electrode under resonance frequency and its validation by laser vibrometer system. (November 2022) - Zhang, Jia-wei; Fu, Geng; Xu, Fan; Zhang, Bin; Tian, Ning; Qin, Sichen
Abstract: Magnetic sensor based on functional dielectric with high-efficiency energy property is projected to stimulate technological advancement in the fields of energy internet, power engineering materials, energy harvesting and storage, touchless human–machine interface, and magnetoreception for artificial intelligence (AI). At present, the research and development of hypersensitive magnetic sensors remain extraordinarily challenging. The effects of magnetoelectric (ME) composite electrodes with different conductivities and their electromechanical resonance frequency of Metal/PZT/Metal laminates were investigated in this paper. The results of calculations and experiments showed that the magnetoelectric coupling in the magnetoelectric composite (Metal/PZT/Metal) was mostly caused by the piezoelectricity effect in the radial direction and Ampere force under DC bias magnetic fields. According to the radial strain measurement, it can be further indicated that the capping layer with high conductivity produced a larger magnetoelectric voltage at the range of resonance frequency. Therefore, the ME voltage coefficient of the silver electrodes was higher than that of the gold electrodes, and they were 77.8 mV/(cm Oe) and 58.3 mV/(cm Oe) at a DC magnetic field of 3000 Oe, respectively. The ME coupling in the ME composite was mostly connected to the piezoelectricity effect and Ampere force, as well as the conductivity of the electrode layer of the ME composite. The optimization of the electrode structures of magnetoelectric composites provides a vital reference for the development of energy storage, information storage and sensing technology in new power systems. Highlights: The magnetoelectric effects of magnetoelectric composite electrodes with different conductivities were investigated. The influence of electrode layer on the magnetoelectric voltage was validated through the laser vibrometer system. The magnetoelectric voltage coefficient of the silver electrodes was higher than that of the gold electrodes.